2018
DOI: 10.3389/fmicb.2017.02678
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Antimicrobial Resistance in Bacteria Using Bioactive Magnetic Nanoparticles and Pulsed Electromagnetic Fields

Abstract: Nisin is a known bacteriocin, which exhibits a wide spectrum of antimicrobial activity, while commonly being inefficient against Gram-negative bacteria. In this work, we present a proof of concept of novel antimicrobial methodology using targeted magnetic nisin-loaded nano-carriers [iron oxide nanoparticles (NPs) (11–13 nm) capped with citric, ascorbic, and gallic acids], which are activated by high pulsed electric and electromagnetic fields allowing to overcome the nisin-resistance of bacteria. As a cell mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The IONPs were activated by high pulsed electric and electromagnetic fields to induce additional permeabilization and local magnetic hyperthermia. The results on the assays on the Gram-positive Bacillus subtilis and Gram-negative E. coli showed that the high pulsed magnetic fields increase the antimicrobial efficiency of nisin loaded on the IONPs, similar to electroporation or magnetic hyperthermia methods, resulting in a synergistic treatment [110].…”
Section: Nanomaterials With Unique Features As Potential Weapons Tmentioning
confidence: 99%
“…The IONPs were activated by high pulsed electric and electromagnetic fields to induce additional permeabilization and local magnetic hyperthermia. The results on the assays on the Gram-positive Bacillus subtilis and Gram-negative E. coli showed that the high pulsed magnetic fields increase the antimicrobial efficiency of nisin loaded on the IONPs, similar to electroporation or magnetic hyperthermia methods, resulting in a synergistic treatment [110].…”
Section: Nanomaterials With Unique Features As Potential Weapons Tmentioning
confidence: 99%
“…Nevertheless, there are physical factors, especially those not common in nature, that bacteria are vulnerable to. Variations in oxygen concentration and temperature have shown changes in bacterial communities, while the use of pulsed electromagnetic field (PEMF) on NPs decorated with nisin protein presents results similar to electroporation or magnetic hyperthermia [ 21 , 22 ]. Other methods include the use of UV light, high hydrostatic pressure, manosonication, a change in pH, and heat shock [ 23 ].…”
Section: Resistance To Physical Factorsmentioning
confidence: 99%
“…High pulsed electric and electromagnetic fields were applied, and Gram-positive Bacillus subtilis and Gram-negative Escherichia coli were utilized as cell models. This strategy increased the antimicrobial efficiency of nisin similar to electroporation or magnetic hyperthermia methods, and a synergistic treatment was also shown to be possible [116].…”
Section: Antimicrobial Activitymentioning
confidence: 99%